2010
DOI: 10.1590/s1807-59322010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Are histological alterations observed in the gallbladder precancerous lesions?

Abstract: INTRODUCTIONGallbladder cancer, which is characterized by rapid progression and a poor prognosis, is a complex disease to treat. Unfortunately, little is known currently about its etiology or pathogenesis. A better understanding of its carcinogenesis and determining risk factors that lead to its development could help improve the available treatment options.METHODBased on this better understanding, the histological alterations (such as acute cholecystitis, adenomyomatosis, xanthogranulomatous cholecystitis, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 32 publications
(38 reference statements)
8
33
2
Order By: Relevance
“…Several studies have reported association between pyloric metaplasia and dysplasia, pyloric metaplasia and cancer and an association between intestinal metaplasia and pyloric metaplasia, dysplasia and cancer (Yamagiwa et al, 1986;Meirelles-costa, 2010). In this study, we observed these changes in and around tumor area, supporting the first hypothesis.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have reported association between pyloric metaplasia and dysplasia, pyloric metaplasia and cancer and an association between intestinal metaplasia and pyloric metaplasia, dysplasia and cancer (Yamagiwa et al, 1986;Meirelles-costa, 2010). In this study, we observed these changes in and around tumor area, supporting the first hypothesis.…”
Section: Discussionsupporting
confidence: 87%
“…[33][35] In our study, metaplasia was identified in 7.67% of the included patients and it was shown to be statistically correlated with H. pylori infection in gallbladder mucosa ( p  = 0.047). Metaplasia is believed to be a strong histological sign for diagnosis of moderate or severe chronic cholecystitis because it is rarely observed in gallbladder autospy in which only mild inflammatory changes present.…”
Section: Discussionsupporting
confidence: 50%
“…These metaplastic mucous cell lineages underlie the development of PanIN lesions in the pancreas. Pyloric metaplasia and intestinal metaplasia have also been noted in association with chronic cholecystitis and implicated in metaplasia to neoplasia progression similar to that in gastric carcinogenesis [4951]. Gastric and intestinal metaplasia lineages are pathognomonic of Barrett’s epithelium and the organization of the metaplastic glands resembles the structure of pyloric glands [52].…”
Section: Identification Of Pyloric Metaplasia In Other Glandular Mucomentioning
confidence: 99%